Alcohol Use Following an Alcohol Challenge and a Brief Intervention among Alcohol‐Dependent Individuals. (January 2014) - Bacio, Guadalupe A.; Lunny, Katy F.; Webb, Jessica N.; Ray, Lara A.
Abstract : Background and Objectives: The study examined the effects of an alcohol challenge on naturalistic drinking among alcohol‐dependent individuals and explored brief motivational interviewing (MI) as a potential intervention for these participants. Method: Alcohol‐dependent individuals ( n = 32, eight females) completed the intake assessment, alcohol challenge, one MI session, and 1‐month follow‐up (87.5% retention) where they completed measures of drinking and motivation for change. Results: As expected, multilevel mixed models revealed that drinking did not increase post‐alcohol challenge. Participants reported a reduction in ambivalence, drinking days, and a trend towards fewer total drinks between the MI and 1‐month follow‐up. Conclusions: Consistent with other studies, the alcohol challenge did not worsen alcohol use. Results support further investigation of brief MI for alcohol‐dependent participants in alcohol challenges. Scientific Significance: Alcohol administration to alcohol‐dependent participants appears to not exacerbate naturalistic drinking. MI may be a feasible intervention for non‐treatment seeking alcohol‐dependent participants in alcohol challenge studies. (Am J Addict 2014;23:96–101)